2020
DOI: 10.1071/ch19227
|View full text |Cite
|
Sign up to set email alerts
|

A Sesquiterpene Isonitrile with a New Tricyclic Skeleton from the Indo-Pacific Nudibranch Phyllidiella pustulosa: Spectroscopic and Computational Studies

Abstract: The sesquiterpene isonitrile, 9-isocyanoneoallopupukeanane 1, has been obtained from the Indo-Pacific nudibranch Phyllidiella pustulosa. The structure of 1, which was investigated by extensive NMR experiments, molecular modelling studies, and density functional calculations, has a different arrangement of the tricyclic ring system compared with other isonitrile metabolites isolated from nudibranchs or sponges. The viability of a biosynthetic pathway leading to 1, proposed to involve a series of carbocation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…The most commonly detected secondary metabolites across the three analysed phyllidiid genera are spongederived sesquiterpene isonitriles and related compounds, which is in accordance with previous chemical investigations of phyllidiid nudibranchs (Burreson et al, 1975;Fusetani et al, 1992;Hirota et al, 1998;Jomori et al, 2015;Kassühlke et al, 1991;Lyakhova et al, 2010;Manzo et al, 2004;Okino et al, 1996;Sim et al, 2020;White et al, 2017;Wright, 2003). Despite extensive chemical studies on marine heterobranchs (see recent reviews by Avila, 2020 andAvila &Angulo-Preckler, 2020), sesquiterpene isonitriles are known only from phyllidiids and two dorid nudibranchs, Cadlina luteomarginata MacFarland, 1966 (Burgoyne et al, 1993;Thompson et al, 1981) and Hexabranchus sanguineus (Rüppell & Leuckart, 1830) (Zhang et al, 2007); both species are considered generalists, feeding on many different sponges.…”
Section: Chemical Analysessupporting
confidence: 87%
See 1 more Smart Citation
“…The most commonly detected secondary metabolites across the three analysed phyllidiid genera are spongederived sesquiterpene isonitriles and related compounds, which is in accordance with previous chemical investigations of phyllidiid nudibranchs (Burreson et al, 1975;Fusetani et al, 1992;Hirota et al, 1998;Jomori et al, 2015;Kassühlke et al, 1991;Lyakhova et al, 2010;Manzo et al, 2004;Okino et al, 1996;Sim et al, 2020;White et al, 2017;Wright, 2003). Despite extensive chemical studies on marine heterobranchs (see recent reviews by Avila, 2020 andAvila &Angulo-Preckler, 2020), sesquiterpene isonitriles are known only from phyllidiids and two dorid nudibranchs, Cadlina luteomarginata MacFarland, 1966 (Burgoyne et al, 1993;Thompson et al, 1981) and Hexabranchus sanguineus (Rüppell & Leuckart, 1830) (Zhang et al, 2007); both species are considered generalists, feeding on many different sponges.…”
Section: Chemical Analysessupporting
confidence: 87%
“…Numerous chemical studies of P. pustulosa have been published (Hirota et al, 1998;Jomori et al, 2015;Kassühlke et al, 1991;Lyakhova et al, 2010;Manzo et al, 2004;Okino et al, 1996;Sim et al, 2020;White et al, 2017;Wright, 2003) as well as our recent publication (Bogdanov et al, 2020) highlighting the chemical variability that is found in nudibranchs commonly encountered and identified as P. pustulosa. Eight P. pustulosa specimens were utilised in this chemical analysis: LCMS revealed three main chemotype variants within the "true" P. pustulosa (see Fig.…”
Section: Phyllidiella Pustulosa (Cuvier 1804)mentioning
confidence: 95%
“…638 An Australian collection of P. pustulosa afforded the moderately antiplasmodial sesquiterpenoid 9-isocyanoneoallopupukeanane 1408 . 639 Antibacterial scalarane 1409 was isolated from the nudibranch Doriprismatica stellata , its dietary sponge Spongia cf. agaricina and also the nudibranch's egg ribbons, where presumably it plays some biological/ecological role.…”
Section: Molluscsmentioning
confidence: 99%
“…The neoallopupukeanane-type sesquiterpene isonitrile, 9-isocyanoneoallopupukeanane ( 114 ), which was characterized by a tricyclo[3.2.1.0.2 3,6 ]decane ring system, was obtained from the Indo-Pacific nudibranch Phyllidiella pustulosa by Garson et al 105 The structure of 114 , which was investigated by extensive NMR experiments, molecular modelling studies, and density functional calculations, has a different arrangement of the tricyclic ring system compared with other isonitrile metabolites isolated from nudibranchs or sponges. The plausible biosynthetic pathway of 114 was proposed to involve a series of carbocation rearrangements, which was explored in a computational study.…”
Section: Terpenesmentioning
confidence: 99%